Persistence of parvovirus B19 in synovial fluid and bone marrow. Issue 7 (July 1995) - Nikkari, S; Roivainen, A; Hannonen, P; Möttönen, T; Luukkainen, R; Yli-Jama, T; Toivanen, P
Abstract : OBJECTIVES–To determine whether parvovirus B19 (B19) persists in rheumatoid arthritis (RA). METHODS–Polymerase chain reaction (PCR) was used to detect parvovirus B19 genome in the synovial fluid cells or peripheral blood mononuclear cells from 61 patients with early RA; bone marrow from one patient was also studied. The synovium or synovial fluid cells from 28 patients with advanced RA, and synovial fluid cell samples from 18 patients with reactive arthritis (as controls) were studied. Two separate sets of primers and probe were used. RESULTS–Parvovirus B19 specific gene sequences were detected in two patients with early arthritis fulfilling the criteria for RA. CONCLUSION–Parvovirus B19 does not play a significant role in the aetiopathogenesis of RA. However, a few cases of a disease indistinguishable from RA may be triggered by parvovirus B19 infection.